Chip dan Antikristus: Suatu Perspektif Etis Teologis - Iin Nur Indrayani Sihombing (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2022)
Abstract: One example that always raises in gossip around the sign of the antichrist (666). When computers were first popularized, some Christians become nervous, because they thought this device was means for the antichrist to rule the world. Now, ironically, it’s hard to find a church that doesn’t have computers. Like wise with the use of barcodes (a kind of striped sign with numbers underneath that is often found on commercial products). Not a few Christians frowned and were super alert when this technology was introduced. Today almost all Christians benefit from this technology.